Results of the experimentation and cultivation of lucerne in Albania - Tahiraj K.; Daci F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Albania is a Mediterranean country very rich of precious wild forage crops. An important part of which are the different species of alfalfa (Medicago spp.). There are 3 important ecotypes of alfalfa in Albania 'Tomin', 'P.K.L', and 'Gjirokastra'. Lucerne has been for a long time an important forage crop in Albania. The scientific research has been concentrated in genetic improvement of local ecotypes, technological aspects of cultivation and seed production. From realized studies it results that local ecotypes 'Tomin' and 'Gjirokastra' have provided about 8-12 per cent production of biomass, dry matter and protein over other varieties. These ecotypes are cultivated in 95 per cent of the surface with Lucerne. Results obtained from some foreign researchers from Albanian local ecotypes have been interesting. The French variety 'Du-Puits' is the best for seed production. Albania has suitable climatic conditions for seed production.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)